Prophylactic Extraction of Third Molars: Evidence-Based Dentistry - Garrocho-Rangel DDS, PhD, Arturo (2017)
This new perspective article was performed to investigate the evidence from published dental literature about the prophylactic extraction of asymptomatic (or disease-free) impacted third molars (ITM) in adolescents and young adults. This clinical procedure is common until today and has been the origin of controversy among the dental community worldwide. However, evidence-based data from well-conducted clinical studies and systematic reviews are not sufficient to justify the routine prophylactic extraction of ITM. Active surveillance at regular intervals has been proposed as a better management strategy. As a conclusion, surgical removal of ITM is only justified in the presence of specific pathosis, independently of the patient’s age.